2022
DOI: 10.3389/fpls.2022.893508
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Promotes Degradation and Metabolism of Residual Fungicides by Inducing UDP-Glycosyltransferase Genes in Tomato

Abstract: Reduced glutathione (GSH) is a key antioxidant, which plays a crucial role in the detoxification of xenobiotics in plants. In the present study, glutathione could reduce chlorothalonil (CHT) residues in tomatoes by inducing the expression of the UDP-glycosyltransferase (UGT) gene. In plants, UGT is an important glycosylation catalyst, which can respond to stresses in time by activating plant hormones and defense compounds. Given the importance of plant growth and development, the genome-wipe analyses of Arabid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
2
6
0
Order By: Relevance
“…These two groups have been found in wheat, as well [54]. In N. benthamiana, 81.63% of the NbUGTs did not contain any introns or contained only one intron, which is consistent with the number of UGT gene introns in tomato, rice, and cotton [51,53,55]. In this study, the website (http://cello.life.nctu.edu.tw/cello.html, accessed on 16 September 2022) was used to predict that these NbUGT genes were primarily located in the cytoplasm, whereas the UGT genes of wheat were mostly located in the cytoplasm, cell membrane, and chloroplast [54], and the UGT genes of cotton were mostly located in the cytosol and chloroplast [56].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…These two groups have been found in wheat, as well [54]. In N. benthamiana, 81.63% of the NbUGTs did not contain any introns or contained only one intron, which is consistent with the number of UGT gene introns in tomato, rice, and cotton [51,53,55]. In this study, the website (http://cello.life.nctu.edu.tw/cello.html, accessed on 16 September 2022) was used to predict that these NbUGT genes were primarily located in the cytoplasm, whereas the UGT genes of wheat were mostly located in the cytoplasm, cell membrane, and chloroplast [54], and the UGT genes of cotton were mostly located in the cytosol and chloroplast [56].…”
Section: Discussionsupporting
confidence: 75%
“…In addition, the implementation of the Human Genome Project (HGP) and the rapid development of high-throughput sequencing technology have provided a vast amount of data for bioinformatics development. UGT genes have been identified and analyzed in many plants, such as maize, cotton, and tomato [ 51 , 52 , 53 ]. N. benthamiana is a heterotetraploid species with 19 chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that GTs play an important role in pesticide detoxification and plant selectivity to herbicides [33][34][35][36]. Zhang et al investigated the metabolism of atrazine after overexpression of the ARGT1 gene in rice (Oryza Ă— sativa) and found that the glycosyltransferase 1 (ARGT1) played an important role in the metabolism and detoxification of atrazine in transgenic rice (Oryza Ă— sativa).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, DON to glutathione conjugation is likely to be a key and distinctive mechanism of DON detoxification determined by the presence of the Fhb7E locus. Interestingly, the further involvement of GSH in detoxification mechanisms was highlighted by a recent study in tomato, where GSH was found to positively regulate the expression of UGT genes in response to a pesticide-induced stress [ 135 ]. If the same crosstalk mechanism among seemingly independent plant protective paths would also be active in our system, it would explain the enhancement of both DON–GSH and D3G observed in Fhb7E carriers compared with the control line.…”
Section: Discussionmentioning
confidence: 99%